Effect of GnRH pulse infusion on LH profiles and ovarian follicle populations at 7 weeks post-partum in beef cows in different body condition - Andrade, L.P. (2013)
Effect og GnRH pulse infusion on LH profiles and ovarian follicle populations at 7 weeks post-partum in beef cows in different body condition.